An evaluation of asymptomatic Dengue infections among blood donors during the 2014 Dengue outbreak in Guangzhou, China. Issue 11 (20th July 2017) - Liao, Qiao; Shan, Zhengang; Wang, Min; Huang, Jieting; Xu, Ru; Huang, Ke; Tang, Xi; Zhang, Weiyun; Nelson, Kenrad; Li, Chengyao; Fu, Yongshui; Rong, Xia
Abstract : In 2014, an outbreak of dengue virus (DENV) infection led to 45 171 clinical cases diagnosed in Guangdong province, Southern China. However, the potential risk of blood donors asymptomatically infected with DENV has not been evaluated . In the current study we detected anti‐DENV IgG antibody and RNA in volunteer Chinese blood donors. We found that anti‐DENV IgG antibody was positively detected in 3.4% (51/1500) and two donors were detected as being DENV RNA positive out of 3000 blood samples. We concluded that the presence of potential DENV in blood donors might be potential risk for blood safety. Therefore, screening for DENV infection should be considered in blood donations during a period of dengue outbreak in high epidemic area of China.